Karakteristik Hukum Islam: Landasan, Prinsip, dan Implementasinya dalam Masyarakat Modern - farhan, muhammad farhan rizaldi (Institut Agama Islam Darul Ulum Kandangan, 2024)
Islamic law has unique characteristics and plays an important role in the lives of society. This article aims to identify the characteristics of Islamic law, analyze its fundamental principles, and examine its implementation in the context of modern society. By understanding the foundations and characteristics of Islamic law, it is hoped that a better insight can be gained regarding the role of this law in everyday life.